2019
DOI: 10.1097/hp.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Remodeling and Reversible Pulmonary Hypertension During Pneumonitis in Rats after 13-Gy Partial-Body Irradiation with Minimal Bone Marrow Sparing: Effect of Lisinopril

Abstract: Total body irradiation causes acute and delayed toxicity to hematopoietic, pulmonary, cardiac, gastrointestinal, renal and other organ systems. Angiotensin converting enzyme (ACE) inhibitors mitigate many of the delayed injuries to these systems. The purpose of this study was to define echocardiographic features in rats at two times after irradiation, the first being before lethal radiation pneumonitis (50 days) and the second after recovery from pneumonitis but before lethal radiation nephropathy (100 days) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For instance, the adult female rats were smaller than agematched adult male rats, with corresponding smaller total lung volumes, and thus a higher percentage of the total lung volume would likely receive radiation using the image-guided radiation setup (Fig. 1), which could contribute to enhanced cardiac changes (25). In any case, both male and female SS rats had worse radiation-induced cardiotoxicity compared with their age-matched SS-3 BN consomic rat counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the adult female rats were smaller than agematched adult male rats, with corresponding smaller total lung volumes, and thus a higher percentage of the total lung volume would likely receive radiation using the image-guided radiation setup (Fig. 1), which could contribute to enhanced cardiac changes (25). In any case, both male and female SS rats had worse radiation-induced cardiotoxicity compared with their age-matched SS-3 BN consomic rat counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…The tolerance dose for loss of lung function was dependent upon the concomitant irradiation of the heart [101][102][103]. Conversely, manifestations of RIHD were more severe when both heart and lungs were exposed [66], and echocardiography after whole thorax or leg-out partial body irradiation revealed changes, including evidence of right-sided heart dysfunction, during periods when radiation pneumonitis was occurring [104,105]. Human studies have also suggested that both heart and lung doses can influence the development of cardiac and/or lung toxicities [14,[106][107][108].…”
Section: Cardiopulmonary Tissue Toxicity From Rtmentioning
confidence: 99%
“…This sophisticated rat model is the first in rodents to express the acute and delayed syndromes of radiation exposure in the same animals. 28 30 In brief, rats were placed in Plexiglas jig. One hind leg was carefully externalized and shielded with a lead block.…”
Section: Methodsmentioning
confidence: 99%